Letters and communities: studies in the socio-political dimensions of ancient epistolography - Ceccarelli, Paola; Doering, Lutz; Fögen, Thorsten; Gildenhard, Ingo (Oxford University Press, 2018)
In the ancient world, letter-writing not only forged connections between individuals, but also helped to construct and cultivate group-identities and communities. This volume explores the interrelation of epistolary communication and socio-political practice across four key cultural configurations: Greece, Rome, Judaism, and Christianity.